Tet Offensive 1968 : turning point in Vietnam - Arnold, James R., 1952-; Arnold, James R., 1952- (London : Osprey, 1990)
"The 1968 Tet Offensive was the decisive battle for Vietnam. Masterminded by the brilliant North Vietnamese General, Vo Nguyen Giap, it was intended to trigger a general uprising in South Vietnam. However, the bloody fighting for Saigon, Hue and other cities actually resulted in a catastrophic defeat for the North. In this excellent assessment of the key battle of the Vietnam conflict, James Arnold details the plans and forces involved and explains how, despite the outcome of the battle, the American people and their leaders came to perceive the war for Vietnam as lost"--Osprey website.
Background to surprise. The plan is born -- Men, weapons and tactics. The Army of the Republic of Vietnam -- The American Infantry -- The Communists -- Communist weapons and tactics -- On the eve -- Tet Saigon. Assaults on the urban centre -- Cavalry to the rescue -- The press reaction -- The Phu Tho racetrack -- Tet Country-wide. Surprise at Da Nang -- Battle in the Delta -- The central highlands -- Bloody Hue. Relief force -- Counter-attack -- The first team -- House-to-house combat -- Assessment.
Includes bibliographical references.
Keywords: 1961-1975; Vietnam War, 1961-1975.; Vietnam Conflict